2023
DOI: 10.48048/tis.2023.6486
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Optimization of Meat, MOCAF (Modified Cassava Flour), and Purified Porang Flour--Carrageenan (PPFC) Mixed Hydrocolloid Gel for Restructured Sliced Meat Formula using Response Surface Methodology

Abstract: This study aims to determine the optimum formula in restructured sliced meat production using the Box-Behnken Design of Response Surface Methodology (BBD-RSM) to obtain the best yield, hardness, and water-holding capacity (WHC). The concentration of the meat used was 30 to 40 %, MOCAF (modified cassava flour) was 10 to 15 %, and purified porang flour-k-carrageenan (PPFC) mixed hydrocolloid gel was 7.5 to 12.5 %. The alterations in yield, hardness, and WHC of restructured sliced meat were significantly predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Moreover, all the responses had R 2 ≥ 0.6536, adjusted R 2 ≥ 0.2083, adequate precision ≥ 4.1399, and lack of fit ≥ 0.0287. The high R 2 and adjusted R 2 demonstrated that the quadratic model adequately explained the variance of all response data [31,32]. Furthermore, adequate precision measures the signal-to-noise ratio, where a ratio ≥ 4 indicates an adequate signal [33,34].…”
Section: Model Fittingmentioning
confidence: 90%
“…Moreover, all the responses had R 2 ≥ 0.6536, adjusted R 2 ≥ 0.2083, adequate precision ≥ 4.1399, and lack of fit ≥ 0.0287. The high R 2 and adjusted R 2 demonstrated that the quadratic model adequately explained the variance of all response data [31,32]. Furthermore, adequate precision measures the signal-to-noise ratio, where a ratio ≥ 4 indicates an adequate signal [33,34].…”
Section: Model Fittingmentioning
confidence: 90%